QUALITY ANALYSIS OF PPL II STUDENT OF MECHANICAL ENGINEERING EDUCATION STUDY PROGRAM IN ACADEMIC YEAR 2014/2015 BASED ON PERCEPTIONS AND EXPECTATIONS - Wiyogo; Yesni Nopy (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2015)
Field Experience Program (PPL) can be defined as a program that imparts a variety of knowledge, attitudes, and skills in order to establish a professional teacher. PPL also prerequisite applicative and integrated capabilities of all previous learning experience in a training program in the form of performance in all matters relating to the position of teacher, both learning activities and tasks of other teacher. Mechanical Engineering Education Study Program (PSPTM) through UP3L FKIP Unpar send students for teaching practice in schools, in this case PSPTM is a manufacturer that foster student and the school as a part of consumers. From the results of studies using Importance Performance Analysis analysis, it is obtained that variables that affect the quality of students is based on the expectations and perceptions of the respondents in the realm plan learning activities found that the factors that must be repaired is like the formulation of specific goals of learning (X12), the determination of teaching aids ( X14), choice of learning activities (X16) and discipline (X25). For the realm of implementation of learning, factors to get priority repair are providing teaching aids and learning resources required (P13), maintaining student’s orderin learning (P28), carry out the assessment during the learning process (P30), a summary (P33). Customer Satisfaction Index of the value of the realm of learning plans to get a value of 54.17% and in the realm of learning activities get an assessment of 58.02%, based on the table Stratford on the range of values ? 51-65% category simply quite satisfactory.